A systematic literature review of computational thinking study in physics learning - Riwayani, Riwayani; Istiyono, Edi; Supahar, Supahar; Perdana, Riki; Jumadi, Jumadi; Soeharto, Soeharto (Institute of Advanced Engineering and Science, 2025)
This systematic review aims to summarize the technological resources for teaching and learning about computational thinking (CT) in physics and provide suggestions to conduct new studies in future research. A total of 22 academic articles on CT in physical learning were reviewed from 2012 to 2022. The number of research participants was 3,269, with details of 2,752 college students, 439 high school students, 32 junior high school students, 20 elementary students, 21 teachers, and five librarians. This study confirmed that research on CT in physical learning has been dominated by two countries, the United States and Indonesia. Over the past 10 years, there has been an increase in physics courses focusing on topics in kinematics, force and motion, and electricity. The common method practices are quantitative and qualitative, with some developing learning. The implications of this research can inform education experts, educators, and technologists interested in the CT environment and technological development in physics learning. Computational skills in physics have the potential to improve cognitive, affective, and psychomotor outcomes, including students’ thinking abilities. Students can benefit from their experience learning physics using the concept of CT because they can solve technology-based problems and develop various competencies needed in learning physics.